Tchad 2008 - Géraud Magrin (EchoGéo)
Since 1965 crises have followed one another in Chad, until the very last episode of February 2008. This paper offers a geographic approach of this last crisis and underlines the importance of the physical setting in the causes and mechanisms of the conflict. Such an approach questions the evolving links between state and societies and between their territories and resources. Internal and external geopolitical dimensions are key factors for a better understanding of the conflict. The vicious circle of rebellion and repression that plagues Chad now needs to be broken. In order to achieve the country's necessary national (re)construction, the state ought, first and foremost, to define a new role for itself if not to reinvent itself altogether. It is only through this (re)construction that the state will find its much needed new legitimacy.